Komunikasi Instruksional dalam Proses Pembelajaran Mahasiswa - Kiki Zakiah Darmawan (Pusat Penerbitan Universitas (P2U) LPPM Unisba, 2006)
Learning process is an important matter in education institution. High competitive among private universities also touched the process of learning as one of facilities being promoted to new students. Based on the concept of instructional communication, this research aimed to describe how communication works to find solutions for learning problems. Instructional communications are consisted of some variables, i.e. the pattern of problem solving activities, specificity of content, and learning objectives. Employing descriptive quantitative methods, the research found that score average of Fikom Unisba students is significant enough to conclude instructional communication as significant factors determining student’s academic achievement.